Treatment of pancreatic cancer with docetaxel and granulocyte colony- stimulating factor: A multicenter phase II study - Androulakis, N.; Kourousis, C.; Dimopoulos, M.A.; Samelis, G.; Kakolyris, S.; Tsavaris, N; Genatas, K.; Aravantinos, G.; Papadimitriou, C.; Karabekios, S.; Stathopoulos, G. P.; Georgoulias, V. (Journal of Clinical Oncology, 1999)
Purpose: To determine the efficacy and tolerance of single-agent docetaxel and granulocyte colony-stimulating factor in patients with advanced pancreatic cancer. Patients and Methods: Thirty-three chemotherapy-naive patients (median age, 65 years) with histologically confirmed pancreatic cancer were treated, after appropriate premedication, with docetaxel (100 mg/m2) and granulocyte colony-stimulating factor (150 μg/m2/d subcutaneously days 2 through 10) every 3 weeks. World Health Organization performance status was 0 to 1 in 28 patients (85%) and 2 in 5 patients (15%). Twenty-nine patients had stage III and IV disease. Results: One complete response (3%) and one partial response (3%) were observed for an overall response rate of 6% (95% confidence interval, 2.1% to 14.2%). Nineteen patients (58%) had stable disease and 12 (36%) had progressive disease. The duration of the two objective responses was 10 and 28 weeks, and the median time to tumor progression was 20 weeks. The median overall survival was 36 weeks. The actuarial 1-year survival was 36.4%. The performance status improved in seven of 21 assessable patients (24%) and pain improved in 14 of 21 (67%) assessable patients; five patients (29%) experienced weight gain during treatment. Disease-related asthenia, anorexia, vomiting, and diarrhea improved in 29%, 15%, 67%, and 47% of the assessable patients, respectively. Serum concentrations of CA 19-9 were decreased by more than 50% in seven patients (35%). Grade 3 and 4 neutropenia occurred in four patients (12%) and eight patients (24%), respectively, with two episodes of febrile neutropenia. There were no treatment-related deaths. Grade 3/4 asthenia occurred in three patients. Conclusion: Although docetaxel has a marginal objective activity in pancreatic cancer, it seems to have an important effect on tumor growth control, conferring a clinical benefit.